2018
DOI: 10.1186/s12935-018-0706-9
|View full text |Cite
|
Sign up to set email alerts
|

Arenobufagin induces MCF-7 cell apoptosis by promoting JNK-mediated multisite phosphorylation of Yes-associated protein

Abstract: BackgroundIt has been demonstrated that bufadienolides exert potent anti-cancer activity in various tumor types. However, the mechanisms that underlie their anti-cancer properties remain unclear. Yes-associated protein, a key effector of Hippo signaling, functions as a transcription coactivator, plays oncogenic and tumor suppressor roles under different conditions. Here, we report that arenobufagin (ABF), a representative bufadienolide, induced breast cancer MCF-7 cells to undergo apoptosis, which occurred thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The compound inhibited cell growth and triggered apoptosis by affecting the expression of Bax and Bcl-2 in the cells (Zhu et al 2018). Arenobufagin also reduced viability of MCF-7 cells and induced apoptosis in a time-and dose-dependent manner (Deng et al 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The compound inhibited cell growth and triggered apoptosis by affecting the expression of Bax and Bcl-2 in the cells (Zhu et al 2018). Arenobufagin also reduced viability of MCF-7 cells and induced apoptosis in a time-and dose-dependent manner (Deng et al 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Arenobufagin also reduced viability of MCF-7 cells and induced apoptosis in a time- and dose-dependent manner (Deng et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous reports showing that ERK usually served as a survival mediator implicated in cytoprotection ( Yao et al., 2012 ; Kikuchi et al., 2013 ), the combined regimen-triggered cytotoxicity was clearly augmented by PD98059, an inhibitor of ERK, suggesting that activation of ERK might compensate for the cytocidal stimuli. Although the activation of JNK has been deeply implicated in apoptosis/necrosis induction in different types of cancer cells ( Deng et al., 2018 ; Qiao et al., 2019 ), inhibition of JNK by SP600125 did not alter the induction of apoptosis/necrosis ( Figure 8 ), suggesting little involvement of JNK activation. Similarly, substantial upregulation of the expression of LC3 was not affected by SP600125 ( Figure 9 ), suggesting that JNK activation and autophagy independently contributed to the cytotoxicity of As III combined with Tetra in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 98%
“…ERK usually serves as a survival mediator implicated in cytoprotection (Kikuchi et al, 2013;Kawiak et al, 2019). On the other hand, JNK and p38 MAPK are generally considered to be involved in cell death induction by diverse stimuli (Hu et al, 2014b;Kikuchi et al, 2014;Deng et al, 2018;Qiao et al, 2019). Of note, recent emerging evidence has demonstrated a strong association between the activation of JNK and antitumor agent-mediated cytotoxicity such as cell cycle arrest as well as autophagic cell death in breast cancer cells (Wang et al, 2016;Xie et al, 2017;Kong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Arenobufagin (ARE, structure shown in Figure 1(a)), one of the effective constituents of toad venom, is a traditional Chinese medicine obtained from the skin and parotid venom glands of Bufo bufo gargarizans Cantor or Bufo melanostictus Schneider [11]. Anyway, a lot of studies have demonstrated its broadspectrum antitumor activities in cancers such as breast cancer, pancreatic carcinoma, and liver cancer [12][13][14]. We previously found that ARE can induce liver cancer cell apoptosis and autophagy through PI3K/Akt/mTOR signal routing [14]; induce cell cycle arrest and apoptosis in human cervical cancer HeLa cells [15]; have anticancer effect on human esophageal squamous cell carcinoma (its mechanism of exerting anticancer efficacy may be activation of cysteinecontaining aspartate proteolytic enzyme (caspase) by endogenous and exogenous pathways); promote apoptosis of esophageal cancer cells by enhancing caspase phosphorylation and activating p53 signaling [16]; promote apoptosis of human glioblastoma U-87 cells by inhibiting p38MAPK signaling pathway [17]; and inhibit epithelial-mesenchymal conversion by going down the β-catenin pathway, consequently repressing motility and invasiveness of prostate cancer PC3 cells [18].…”
Section: Introductionmentioning
confidence: 99%